2016
DOI: 10.3109/00207454.2016.1170015
|View full text |Cite
|
Sign up to set email alerts
|

The effects of forest therapy on depression and anxiety in patients with chronic stroke

Abstract: Forest therapy is beneficial for treating depression and anxiety symptoms in patients with chronic stroke, and may be particularly useful in patients who cannot be treated with standard pharmacological or electroconvulsive therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
203
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(214 citation statements)
references
References 20 publications
8
203
0
3
Order By: Relevance
“…It was found that spending time in a forest can effectively reduce mental stress and alleviate anxiety (Morita et al 2007, Kim et al 2009, Park et al 2011, Ochiai et al 2015, Song et al 2016, Chun et al 2016. This function was recognized as the term of "forest bathing", i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that spending time in a forest can effectively reduce mental stress and alleviate anxiety (Morita et al 2007, Kim et al 2009, Park et al 2011, Ochiai et al 2015, Song et al 2016, Chun et al 2016. This function was recognized as the term of "forest bathing", i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that forest bathing can make people feel relaxed and comfortable with more anxiety-alleviation than walking in a local urban environment (Song et al 2013, Sonntag-Öström et al 2015a, Chun et al 2016. In addition, the negative mood of exhaustion-disorder and hypertensive patients was regulated by forest bathing after repeated visits for several months in the forest (Sonntag-Öström et al 2015a, Chun et al 2016) and mood of chronic stroke patients can be improved by 3-4 days of forest bathing (Chun et al 2016). Taking ordinary people as participants, it was found that their anxiety can also be alleviated in 1-2 days (Park et al 2007, 2011, Lee et al 2009, Ochiai et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the study design, 11 studies used a crossover trial design and only six of the studies [16,[18][19][20][21][22] used a randomized controlled trial (RCT) design. Four out of six RCT design studies were conducted with adults with health problems.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…For articles published in English, nine studies [12,19,21,22,25,28,29,34,39] used POMS to assess the level of depression and three studies [28,29,39] used Semantic differential (SD) method. Other scales used by the studies included the Hamilton Rating Scales for Depression [20], Beck Depression Inventory (BDI) [16,20,24,31], positive and negative affect schedule (PANAS) [34]. For studies published in Korean, the POMS [15,23,26,27,32,38] and BDI [13][14][15]17,18,35] were the most commonly used scale.…”
Section: Depression Measuresmentioning
confidence: 99%
See 1 more Smart Citation